MULTICULTURAL LITERATURE FOR A PEACE-BASED PROSE CLASS FOR EFL TEACHER EDUCATION - Purwanti Kusumaningtyas (Indonesian JELT, 2011)
The recent phenomena of religious based violence and terrorism in Indonesia shows that the target recruits of fundamentalist groups and institution members are students from higher education (Saragih, 2011). English language classrooms are in fact potential as peace agency as the teachers  are in a strategic position to influence infrastructure, to invest in their social capital and to construct moral imagination (Anderson 1991, Birch 2009) as language is not a mere means of communication, but it is more a means to construct realities. In response to today’s need for a peaceful environment in Indonesia, English teachers must be aware and be proactive agents to promote a more dialogic atmosphere in their classrooms. This paper will discuss how Prose class with peace-based language learning perspective made use of Richard Oh’s Novel “The Pathfinders of Love.” The story is a meaningful material to encourage students’ self-awareness as a part of the diversed society and to promote dialogic relation among themselves. The paper will first provide a detailed description of the class participants and their different background, then outline  a brief analysis of the issues of conflict and peace in the story, and present an elaborate discussion of how the in-class and out-class activities promote a deeper understanding of what peace means in a multicultural environment. Keywords:      multicultural literature, peace-based language teaching, EFL teacher education